Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
3z-4=6z-17
-3z-4=-17 (subtracted the 6z from both sides)
-3z=-13 (added the 4 to both sides)
z=[tex] \frac{-13}{-3z} [/tex] (divided both sides by -3z)
z=[tex] \frac{13}{3} [/tex]
-3z-4=-17 (subtracted the 6z from both sides)
-3z=-13 (added the 4 to both sides)
z=[tex] \frac{-13}{-3z} [/tex] (divided both sides by -3z)
z=[tex] \frac{13}{3} [/tex]
3z - 4 = 6z - 17. First try to take all the zs to one side of the equation
preferrably to the left. And the sign of any expression
changes on crossing the equality sign.
3z-6z = -17+4
-3z = +4-17
-3z = - 13. Divide both sides by -3.
-3z/-3 = -13/-3
z = 13/3.
preferrably to the left. And the sign of any expression
changes on crossing the equality sign.
3z-6z = -17+4
-3z = +4-17
-3z = - 13. Divide both sides by -3.
-3z/-3 = -13/-3
z = 13/3.
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.